A robust measurement point for dose verification in delivery quality assurance for a robotic radiosurgery system. (3rd November 2016) - Kurosu, Keita; Sumida, Iori; Shiomi, Hiroya; Mizuno, Hirokazu; Yamaguchi, Hiroko; Okubo, Hirofumi; Tamari, Keisuke; Seo, Yuji; Suzuki, Osamu; Ota, Seiichi; Inoue, Shinichi; Ogawa, Kazuhiko
Abstract: In this CyberKnife® dose verification study, we investigated the effectiveness of the novel potential error (PE) concept when applied to the determination of a robust measurement point for targeting errors. PE was calculated by dividing the differences between the maximum increases and decreases in dose distributions by the original distribution after obtaining the former by shifting the source-to-axis and off-axis distances of each beam by ±1.0 mm. Thus, PE values and measurement point dose heterogeneity were analyzed in 48 patients who underwent CyberKnife radiotherapy. Sixteen patients who received isocentric dose delivery were set as the control group, whereas 32 who received non-isocentric dose delivery were divided into two groups of smaller PE (SPE) and larger PE (LPE) by using their median PE value. The mean dose differences (± standard deviations) were 1.0 ± 0.9%, 0.5 ± 1.4% and 4.1 ± 2.8% in the control, SPE and LPE groups, respectively. We observed significant correlations of the dose difference with the PE value ( r = 0.582, P < 0.001) and dose heterogeneity ( r = 0.471, P < 0.001). We concluded that when determining a robust measurement point for CyberKnife point dose verification, PE evaluation was more effective than the conventional dose heterogeneity-based method that introduced optimal measurement point dose heterogeneity of <10% across the detector.